Vachel Lindsay’s Visionary Theoretical Reflections on Film - Srebrenka Mačković (Društvene i Humanističke Studije, 2023)
Although neglected for decades, American poet, journalist, and painter Nicholas Vachel Lindsay (1879-1931) made a significant contribution to the rising film theory with his book The Art of The Moving Picture, the first American study of a kind, published in 1915. Having noticed the widespread popularity of silent movies among the millions of film lovers in the USA, Lindsay proposed that this new visual art form, which, according to him, represented a combination of a traditional theatre play and diverse elements of painting, sculpture, architecture and other forms of visual expression that he called photoplay, could, in due time, become a truly American art brand. For that reason, he advocated the establishment of film schools, film libraries and archives, as well as the use of film for educational purposes in schools. This paper analyzes Lindsay’s key theoretical tenets of film as an important fine art as presented in his book The Art of The Moving Picture, as well as his visionary predictions regarding the later development of film (and later television) as not just lucrative, commercial products, but also an interesting field of academic study.